Physiological profiles of elite off-road and road cyclists - Wilber, R. L.; Zawadzki, K. M.; Kearney, J. T.; Shannon, M. P.; Disalvo, D. (Medicine & Science in Sports & Exercise, 1997)
There are minimal scientific data describing international caliber off-road cyclists (mountain bikers), particularly as they compare physiologically with international caliber road cyclists. Elite female (N = 10) and male (N = 10) athletes representing the United States National Off-Road Bicycle Association (NORBA) Cross-Country Team were compared with elite female (N = 10) and male (N = 10) athletes representing the United States Cycling Federation (USCF) National Road Team. Submaximal and maximal exercise responses were evaluated during the "championship" phase of the training year when athletes were in peak condition. All physiological tests were conducted at 1860 m. Among the female athletes, physiological responses at lactate threshold (LT) and during maximal exercise (MAX) were similar between NORBA and USCF cyclists with two exceptions: 1) USCF cyclists demonstrated a significantly greater (P < 0.05) absolute (16%) and relative (10%) maximal aerobic power, and 2) MAX heart rate was significantly higher (P < 0.05) for the USCF athletes (6%). Among the male athletes, physiological responses at LT and MAX were similar between NORBA and USCF cyclists with two exceptions: 1) USCF cyclists produced significantly greater (P < 0.05) absolute (18%) and relative (16%) power at LT, and 2) USCF cyclists produced significantly greater (P < 0.05) absolute (12%) and relative (10%) power at MAX. These data suggest that, in general, elite off-road cyclists possess physiological profiles that are similar to elite road cyclists.